2010
DOI: 10.3109/0886022x.2010.494805
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced changes in renal URAT1 activity and expression in rats

Abstract: During exercise, the plasma urate levels and urinary excretion increase due to the enhanced purine degradation in skeletal muscle. Although urate transporter-1 (URAT1) is the main transporter responsible for the reabsorption of filtered urate, potential changes in its activity and expression during exercise have not been studied yet. Therefore, the effect of heavy muscle activity on renal URAT1 activity and expression was investigated in this study. Wistar rats were used in the study and the experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies showed that URAT1 expression in HUA individuals was higher than in healthy individuals 46,47 . URAT1 protein activity increased after exercise in healthy rats 6 , and this study proposed that exercise-induced changes in URAT1 expression and activity were associated with increased blood urate levels. However, our results suggest that changes in URAT1 expression after exercise are not solely related to SUA levels.…”
Section: Discussionmentioning
confidence: 83%
“…Studies showed that URAT1 expression in HUA individuals was higher than in healthy individuals 46,47 . URAT1 protein activity increased after exercise in healthy rats 6 , and this study proposed that exercise-induced changes in URAT1 expression and activity were associated with increased blood urate levels. However, our results suggest that changes in URAT1 expression after exercise are not solely related to SUA levels.…”
Section: Discussionmentioning
confidence: 83%
“…Alternatively, URAT1 protein levels may not accurately predict transporter activity. Others have shown a decrease in the 60 kDa URAT1 transcript in cortex with exercise and hyperuricemia in rats, associated with elevated URAT1 mediated urate reabsorption [39]. Alternatively spliced transcripts may also have non-coding regulatory functions [40].…”
Section: Discussionmentioning
confidence: 99%